KESULITAN GURU DALAM PENGGUNAAN MEDIA PEMBELAJARAN DI SEKOLAH DASAR - Rizki Ananda; Tamara Sartiwi; Diva Zahra; Tia Rama Danti; Vina Adil Fitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the difficulties experienced by teachers in using learning media in elementary schools. The research method used is descriptive qualitative with a case study approach, involving teachers in grades 4 to 6 in one of the public elementary schools as subjects. Data were collected through in-depth interviews, participant observation, and documentation. The results of the study indicate that teachers face various obstacles in using learning media, including limited access and infrastructure, low technological skills, limited preparation time, resistance to change, and varying student conditions. These findings emphasize the need for comprehensive support from schools, government, and the community to improve teacher capacity and equalize educational facilities.